2014
DOI: 10.1186/2054-7072-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalic Parkinsonism: lessons from normal pressure hydrocephalus mimics

Abstract: BackgroundHydrocephalus is an under-recognized presentation of progressive supranuclear palsy (PSP) and dementia with Lewy bodies (DLB).MethodsWe describe four normal pressure hydrocephalus (NPH)-like presentations of pathology-proven PSP (n = 3) and DLB (n = 1) and review the literature on the hydrocephalic presentation of these atypical parkinsonisms.ResultsDespite the presence of ventriculomegaly disproportionate to the extent of parenchymal atrophy, all patients demonstrated early postural impairment and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 13 publications
2
34
0
1
Order By: Relevance
“…As in our study, neurodegenerative diseases are frequent causes of poor outcome after VP-shunting [22]. The extrapyramidal symptoms of these diseases can mimic the symptoms of patients with NPH [36]. Even these patients can improve temporarily after VP-shunting [10].…”
Section: Risk Factorssupporting
confidence: 62%
“…As in our study, neurodegenerative diseases are frequent causes of poor outcome after VP-shunting [22]. The extrapyramidal symptoms of these diseases can mimic the symptoms of patients with NPH [36]. Even these patients can improve temporarily after VP-shunting [10].…”
Section: Risk Factorssupporting
confidence: 62%
“…However, with the help of the recent reports including pathological examinations, many discussions and hypotheses have been suggested about this topic. 1,9,10 For instance, Starr et al postulated that previously reported cases of "dual" pathology (e.g., NPH and PSP) actually represent the hydrocephalic presentation of selected neurodegenerative disorders. 9 Moreover, in his crucial report, Saper remarked the controversies regarding the definition of iNPH.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,10 For instance, Starr et al postulated that previously reported cases of "dual" pathology (e.g., NPH and PSP) actually represent the hydrocephalic presentation of selected neurodegenerative disorders. 9 Moreover, in his crucial report, Saper remarked the controversies regarding the definition of iNPH. 10 He mentioned that in many related studies on shunting for iNPH had required only two or even one of these symptoms to include the patient in the series.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the clinical picture of iNPH often overlaps with the symptoms of other neurodegenerative diseases, including dementias such as Alzheimer’s disease (AD) and dementia with Lewy bodies, or extrapyramidal spectrum disorders including Parkinson’s disease (PD), progressive supranuclear palsy (PSP), and corticobasal syndrome [1, 6]. This is not unexpected given that iNPH is also considered a neurodegenerative disorder [6–8], and that symptoms of different neurodegenerative diseases often coexist. Indeed, these problems can make precise diagnosis impossible before death and postmortem analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these problems can make precise diagnosis impossible before death and postmortem analysis. Even then, a coexistence of multiple types of pathological processes can be found in the brain [6–13]. Thus, identification of specific biomarkers is important to improve accurate diagnosis and for use of most appropriate treatmentstrategies.…”
Section: Introductionmentioning
confidence: 99%